FBXO38 is dispensable for PD-1 regulation - Dibus, Nikol; Salyova, Eva; Kolarova, Karolina; Abdirov, Alikhan; Pagano, Michele; Stepanek, Ondrej; Cermak, Lukas (EMBO reports, 2024)
SKP1-CUL1-F-box protein (SCF) ubiquitin ligases are versatile protein complexes that mediate the ubiquitination of protein substrates. The direct substrate recognition relies on a large family of F-box-domain-containing subunits. One of these substrate receptors is FBXO38, which is encoded by a gene found mutated in families with early-onset distal motor neuronopathy. SCFFBXO38 ubiquitin ligase controls the stability of ZXDB, a nuclear factor associated with the centromeric chromatin protein CENP-B. Loss of FBXO38 in mice results in growth retardation and defects in spermatogenesis characterized by deregulation of the Sertoli cell transcription program and compromised centromere integrity. Moreover, it was reported that SCFFBXO38 mediates the degradation of PD-1, a key immune-checkpoint inhibitor in T cells. Here, we have re-addressed the link between SCFFBXO38 and PD-1 proteolysis. Our data do not support the notion that SCFFBXO38 directly or indirectly controls the abundance and stability of PD-1 in T cells.
Keywords: T-Lymphocytes; Immune Checkpoint; PD-1; F-box proteiny; antigeny CD279; T-lymfocyty; mužské pohlaví; ubikvitinace; Mice; Programmed Cell Death 1 Receptor; Ubiquitination; proteolýza; Proteolysis; Protein Degradation; F-Box Proteins; zvířata; Humans; Cullin; FBXO38; myši; proteinligasy komplexu SCF; SKP Cullin F-Box Protein Ligases; lidé; Male; Animals